Cigarettes and e-cigarettes use among US adults with multimorbidity - Olatokunbo Osibogun; Wei Li; Rime Jebai; Mohammad Ebrahimi Kalan (Drug and Alcohol Dependence Reports, 2024)
Background: Tobacco use leads to multiple illnesses. Yet, the effects of different categories of tobacco use on multimorbidity remain understudied. We investigated the associations between tobacco use categories and multimorbidity and the potential moderating effects of age, sex, or race/ethnicity among adults in the United States. Methods: We conducted a cross-sectional analysis using pooled data from the Behavioral Risk Factor Surveillance System for the years 2020–2022. Multimorbidity was ascertained through self-reported ≥2 chronic health conditions. We categorized tobacco use into nine derived from nonuse (did not use e-cigarettes or cigarettes), former cigarette or e-cigarette use, current (used on some days/everyday) cigarette use or e-cigarette use, or both (dual use). We used multinomial logistic regression to investigate the associations while accounting for potential confounding factors. Results: Within the sample (N=1,080,257), 28.2% reported multimorbidity. For the categories examined (former exclusive e-cigarette, exclusive e-cigarette, former exclusive cigarette, former dual, former cigarette/current e-cigarette, exclusive cigarette, current cigarette/former e-cigarette and dual use), all reported higher odds of having multimorbidity compared to those who reported nonuse of both e-cigarettes and cigarettes. We found significant interactions for age, sex and race/ethnicity with the tobacco use categories for multimorbidity (p<0.01), where stronger associations were observed among younger adults, females and non-Hispanic Multiracial for current dual use (p<0.05). Conclusions: The use of cigarettes, e-cigarettes, or both was associated with multimorbidity among adults, which was more pronounced among younger adults, females and non-Hispanic Multiracial. These findings underscore the importance of implementing targeted public health interventions to mitigate the health risks associated with using both products, particularly among specific demographics, to reduce the prevalence of multimorbidity.